Longitudinal Model of Periprosthetic Joint Infection in the Rat. Issue 5 (23rd December 2019) - Fan, Yingfang; Xiao, Yinbo; Sabuhi, Wali A.; Leape, Charlotte P.; Gil, Dmitry; Grindy, Scott; Muratoglu, Orhun K.; Bedair, Hany; Collins, Jamie E.; Randolph, Mark; Oral, Ebru
ABSTRACT: The majority of periprosthetic joint infections occur shortly after primary joint replacement (<3 months) and require the removal of all implant components for the treatment period (~4 months). A clinically relevant animal model of periprosthetic infection should, therefore, establish an infection with implant components in place. Here, we describe a joint replacement model in the rat with ultrahigh molecular weight polyethylene (UHMWPE) and titanium components inoculated at the time of surgery by methicillin‐sensitive Staphylococcus aureus ( S. aureus ), which is one of the main causative microorganisms of periprosthetic joint infections. We monitored the animals for 4 weeks by measuring gait, weight‐bearing symmetry, von Frey testing, and micro‐CT as our primary endpoint analyses. We also assessed the infection ex vivo using colony counts on the implant surfaces and histology of the surrounding tissues. The results confirmed the presence of a local infection for 4 weeks with osteolysis, loosening of the implants, and clinical infection indicators such as redness, swelling, and increased temperature. The utility of specific gait analysis parameters, especially temporal symmetry, hindlimb duty factor imbalance, and phase dispersion was identified in this model for assessing the longitudinal progression of the infection, and these metrics correlated with weight‐bearing asymmetry. We propose to use this model to study the efficacy of using different local delivery regimens of antimicrobials on addressing periprosthetic joint infections. Statement of clinical significance: We have established a preclinical joint surgery model, in which postoperative recovery can be monitored over a multi‐week course by assessing gait, weight‐bearing, and allodynia. This model can be used to study the efficacy of different combinations of implant materials and medication regimens. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:1101‐1112, 2020